Non-Medical Switching or Discontinuation Patterns among Patients with Non-Valvular Atrial Fibrillation Treated with Direct Oral Anticoagulants in the United States: A Claims-Based Analysis - Michael Ingham; Hela Romdhani; Aarti Patel; Veronica Ashton; Gabrielle Caron-Lapointe; Anabelle Tardif-Samson; Patrick Lefebvre; Marie-Hélène Lafeuille (Journal of Market Access & Health Policy)
This study assessed direct-acting oral anticoagulant (DOAC) switching/discontinuation patterns in patients with non-valvular atrial fibrillation (NVAF) in 2019, by quarter (Q1–Q4), and associated socioeconomic risk factors. Adults with NVAF initiating stable DOAC treatment (July 2018–December 2018) were selected from Symphony Health Solutions’ Patient Transactional Datasets (April 2017–January 2021). Switching/discontinuation rates were reported in 2019 Q1–Q4, separately. Non-medical switching/discontinuation (NMSD) was defined as the difference between switching/discontinuation rates in Q1 and mean rates across Q2–Q4. The associations of socioeconomic factors with switching/discontinuation were assessed. Of 46,793 patients (78.7% ≥ 65 years; 52.6% male; 7.7% Black), 18.0% switched/discontinued their initial DOAC in Q1 vs. 8.8% on average in Q2–Q4, corresponding to an NMSD of 9.2%. During the quarter following the switch/discontinuation, more patients who switched/discontinued in Q1 remained untreated (Q1: 77.0%; Q2: 74.3%; Q3: 71.2%) and fewer reinitiated initial DOAC (Q1: 17.6%; Q2: 20.8%; Q3: 24.0%). Factors associated with the risk of switching/discontinuation in Q1 were race, age, gender, insurance type, and household income (all p < 0.05). More patients with NVAF switched/discontinued DOACs in Q1 vs. Q2–Q4, and more of them tended to remain untreated relative to those who switched/discontinued later in the year, suggesting a potential long-term impact of NMSD. Findings on factors associated with switching/discontinuation highlight potential socioeconomic discrepancies in treatment continuity.